Dimensi Identitas Pi’il Pesenggiri Ulun Lampung dalam Pengembangan Konseling Indigenous: Suatu Tinjauan Sistematis - Shinta Mayasari; Mujiyati Mujiyati; Ashari Mahfud (Universitas Mathla'ul Anwar Banten, 2022)
DIMENSIONS OF PI'IL PESENGGIRI ULUN LAMPUNG'S IDENTITY IN INDIGENOUS COUNSELING DEVELOPMENT: A SYSTEMATIC REVIEW. This research was conducted to find out and understand the meaning of pi'il pesenggiri as one of the dimensions of Lampung's ulun identity in the development of indigenous counseling. The method used is a systematic review of a number of articles about pi'il pesenggiri in reputable journals. A search on journal databases such as DOAJ, microsoft academic, and researchgate found 234 journals with the keyword pi'il pesenggiri. Furthermore, the journals were collected for a screening process and their eligibility according to the inclusion and exclusion criteria determined by the researcher. Based on the screening process, 5 articles were obtained which were the subject of research studies. The results showed that pi'il pesenggiri is the philosophy of life of ulun Lampung which refers to self-esteem and honor. Includes aspects of 1) Bejuluk Adek, 2) Nemui Nyimah, 3) Nengah Nyappur, and 4) Sakai Sambaiyan. The value of pi'il pesenggiri can be a potential in the development of customary extension. These values ​​can be the basis for increasing the multicultural competence of counselors in terms of understanding and knowledge of local wisdom. This is based on the content possessed by pi'il pesenggiri for ulun Lampung in the form of divine values ​​(holiness), religious values, spiritual values, moral values, intellectual values, individual values, social values, and material values. These values ​​can be re-condensed into divine values, human values, and life values.